Innate Immunity at the Core of Sex Differences in Osteoarthritic Pain? - Valdrighi, Natália; Vago, Juliana P.; Blom, Arjen B.; Loo, Fons A.J. van de; Blaney Davidson, Esmeralda N. (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is a progressive whole-joint disease; no disease-modifying drugs are currently available to stop or slow its process. Symptoms alleviation is the only treatment option. OA is the major cause of chronic pain in adults, with pain being the main symptom driving patients to seek medical help. OA pathophysiology is closely associated with the innate immune system, which is also closely linked to pain mediators leading to joint pain. Pain research has shown sex differences in the biology of pain, including sexually dimorphic responses from key cell types in the innate immune system. Not only is OA more prevalent in women than in men, but women patients also show worse OA outcomes, partially due to experiencing more pain symptoms despite having similar levels of structural damage. The cause of sex differences in OA and OA pain is poorly understood. This review provides an overview of the involvement of innate immunity in OA pain in joints and in the dorsal root ganglion. We summarize the emerging evidence of sex differences regarding innate immunity in OA pain. Our main goal with this review was to provide a scientific foundation for future research leading to alternative pain relief therapies targeting innate immunity that consider sex differences. This will ultimately lead to a more effective treatment of pain in both women and men.